Smoking dependence and anxio-depressive disorders in Tunisian smokers attending the smoking cessation clinic in a university hospital - Héla Ghali; Oussama Ben Rejeb; Sihem Ben Fredj; Salwa Khéfacha; Lamine Dhidah; Mohamed Ben Rejeb; Houyem Said Latiri (Journal of the Egyptian Public Health Association, 2019)
Abstract Background Smokers with comorbid anxio-depressive disorders are more prone to progress to a more severe level of dependence and to experience more severe nicotine withdrawal symptoms than smokers without anxio-depressive disorders. Aim of the study To determine the relationship between tobacco dependence and anxio-depressive disorders as well as assessing their impact on the withdrawal. Methods We conducted a cross-sectional study among attendees of the smoking cessation clinic of Sahloul University Hospital, Sousse, Tunisia, from December 2009 to May 2015. The monitoring of the attendees was performed through retrieving the records until May 2016 in order to verify their smoking cessation status at 1 year. Results Overall, 534 smokers were included. We identified 315 smokers (59%) presenting an anxio-depressive disorder. Based on the HAD scale, we found 231 patients (43.4%) with anxiety disorders, 200 (37.6%) patients with depressive disorders, and 116 (21.8%) patients with anxio-depressive disorder. In multivariate analysis, only a high number of consultation was associated with a better rate of tobacco cessation at 6 months. However, no factor was found linked to the relapse at 1 year. Conclusion According to our results, only a high number of consultation was revealed as an independent factor of withdrawal for anxio-depressed smokers. It is necessary to simultaneously use the nicotinic substitutions and anxio-depressive treatment to ensure the tobacco cessation.